Pengaruh Tax Relaxation, Morale, Incentive Terhadap Tax Compliance Pasca Covid-19 - Pebe Manda Sari, Ngadiman (Jurnal Paradigma Akuntansi, 2021)
This study has a purpose, namely to prove the influence of Tax Relaxation, Tax Morale, Tax Incentive on Tax Compliance in Indonesia after pandemic Covid-19. This study took the sample using the Non-Probability Sampling method with the Accidental approach. This study was conducted on people who have a NPWP and only distributed to tax payers who are aware of Tax Relaxation in Jakarta and understand tax incentives. The total sample used in this study were 78 respondents. Research data were processed using SmartPLS ( Partial Least Square) Version 3. The result of this study indicate that the influence of Tax Relaxation & Tax Morale have a significant positive effect on Tax Compliance while the research results for tax incentives show a significant effect on tax compliance.